Replicability. Politics and Poetics of Accountability, Validation and Legitimation - Gobo, Giampietro (Frontiers in Psychology, 2021)
Replicability is a term that not only comes with different meanings in the literature of many domains but is often associated or confused with other terms such as ‘reproducibility’, ‘repeatability’, ‘reliability’, ‘validity’ and so on. To add to the confusion, it can even be used differently across diverse disciplines. Though all named concepts are important, what makes them barely advantageous is that they do not cover some peculiar aspects of the replicability and validation processes, i.e. appropriateness of conceptualization; trustworthiness of operational definition and operational acts; accuracy of researcher’s description, categorization and/or measurement; successfulness of observational (or field) relation. Moreover, in social sciences and organization studies, the concept of validity of data is highly questionable due to the quite frequent shortage of real statuses of the observed objects. The present paper aims to challenge the received view on the concept of ‘replicability’, by proposing a “situational approach” based on the idea that replicability works under certain organizational and socio-technic conditions, and that it is heavily influenced by the way that different stakeholders (scientists, technicians, participants artifacts and technologies respond to them. Consequently, it is important to understand how and why replicability works in different contexts. Its main purpose, without denying the importance of current conventional perspectives on replicability and its siblings, is to widen and change them to include an organizational setting and a reflexive epistemology. This implies the pursuit of a third way of replicability, between the postmodernist negation of its possibility and its opposite, i.e. a naïve naturalism. A way asserting that replicability is a jigsaw puzzle or a mosaic, constituted by discursive practices (poetics) and organizational achievements guiding the politics of accountability, validation and legitimation. The domain here considered pertains to the social and organizational sciences. However, though going beyond the aim of this essay, many issues could be reframed and adapted to medical, natural and physical sciences, as some of the following examples can show.